Evaluation of the Child-Friendly City Policy in Padang City (A Study on the Level of Violence Against Children) - Arif, Muhammad Ananda; Magriasti, Lince (The Future of Education Journal, 2025)
This research is motivated by the increasing cases of violence against children in Padang City despite the government having implemented a Child-Friendly City (KLA) policy based on Regional Regulation No. 12 of 2019. The purpose of this study is to evaluate the effectiveness of the implementation of the KLA policy in reducing the number of child violence cases and identify the obstacles faced. This study uses a qualitative approach with descriptive methods through interviews, observation, and documentation from related agencies such as DP3AP2KB, P2TP2A, and Puspaga. The results show that despite a strong commitment from the local government and the availability of various programs such as Puspaga and PATBM services, the implementation of the policy has not been effective in reducing the number of child violence cases. Based on William N. Dunn's six evaluation criteria, weaknesses were found in the aspects of effectiveness, efficiency, equity, and responsiveness due to weak cross-sectoral coordination, limited facilities, and low community participation. This study concludes that the Child-Friendly City policy in Padang City has a strong legal basis but has not been fully targeted. The implications of this research emphasize the need to strengthen inter-agency coordination, increase the budget and facilities for children's services, and expand public education to create a truly safe and child-friendly urban environment.